Producing, reproducing, and preserving : magazines and anthologies from the Harlem Renaissance and the Black Arts Movement in the formation of an African-American literary canon - (:unkn) unknown (My University, 2021)
The Harlem Renaissance and the Black Arts Movement were two periods, characterized by an artistic and editorial outburst, which contributed to outline the African-American literary canon. This dissertation examines the editorial history of magazines and anthologies published during these periods in order to shed light on various canon-formation processes specific to this literature. Studying publications which, on the whole, have seldom elicited comments reveals that the circumstances of production, reproduction and preservation of texts influence how the latter are evaluated from a literary and aesthetic standpoint.The present work highlights how multiple social, political, economic, intellectual or editorial factors have had a direct sway on the African-American literary production, by serving as thematic inspiration, by limiting spaces of expression or, on the contrary, by fostering the creation of new publications. Thanks to the successive reproductions of the same texts, it is possible to see a literary tradition emerge almost imperceptibly. However, anthologists have repeatedly offered various interpretations of this tradition, reducing or expanding its scope. It betrays the instability of this tradition which changes from one volume to the next, and from era to era. The different methods involved in the preservation of literature are practices and policies which are likely to alter substantially the status of literary works and, by extension, to allow for the African-American literary canon to be redefined
Keywords: African Research